Practical advice for extracellular vesicle isolation in plant–microbe interactions: Concerns, considerations, and conclusions - Hannah Thieron; Laura Krassini; Seomun Kwon; Sebastian Fricke; Sabrine Nasfi; Lorenz Oberkofler; Alessa Ruf; Julia Kehr; Karl‐Heinz Kogel; Arne Weiberg; Michael Feldbrügge; Silke Robatzek; et al. (Journal of Extracellular Vesicles)
Abstract In recent years, extracellular vesicles (EVs) have emerged as novel key players in plant–microbe interactions. While it is immensely useful to draw on the established “minimal information for studies of extracellular vesicles” (MISEV) guidelines and precedents in mammalian systems, working with plants and their associated microbes poses specific challenges. To navigate researchers through these obstacles, we offer detailed step‐by‐step suggestions for those embarking on EV research in the context of plant–microbe interactions. The advice is based on recent publications and our collective experience from the diverse plant and microbe systems studied in a dedicated research consortium. We provide considerations for experimental design, optimization, quality control, and recommendations on how to increase yield, purity, and reproducibility of EV isolation. With this perspective article, we aim not only to assist researchers in our field but also to promote discussions on plant and microbe EVs in the broader EV community.